2007
DOI: 10.1055/s-2006-957070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of Lichen-Derived Compounds against Methicillin- and Multidrug-Resistant Staphylococcus aureus

Abstract: The inhibitory effects of selected phenolic lichen substances were tested against a panel of methicillin- and multidrug-resistant Staphylococcus aureus. Depsidones with long alkyl chains on both of the aromatic rings were consistently active against the strains tested, comparable to or better than the level of clinically used antibacterial drugs. A similar level of activity was also observed for rhizocarpic acid. The previously described cytotoxic pentacyclic compound hybocarpone was by far the most active, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 19 publications
2
29
2
Order By: Relevance
“…Various studies have shown similar results (Kokubun et al, 2007;Pompilio et al, 2013). Extracts from nine of our tested lichen species showed relatively low MIC values (516 mg/ml) against the methicillin-resistant S. aureus and extracts from Rhizoplaca marginalis and Usnea hirta had the lowest values at 7.8 mg/ml.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Various studies have shown similar results (Kokubun et al, 2007;Pompilio et al, 2013). Extracts from nine of our tested lichen species showed relatively low MIC values (516 mg/ml) against the methicillin-resistant S. aureus and extracts from Rhizoplaca marginalis and Usnea hirta had the lowest values at 7.8 mg/ml.…”
Section: Discussionsupporting
confidence: 76%
“…Since Burkholder et al (1944) first reported on the antibiotic properties of lichens, a number of studies have investigated the antimicrobial activities of several lichen species against various Gram-positive, Gram-negative, and mycobacteria (Hobbs, 1986;Ingólfsdóttir et al, 1985;Kokubun et al, 2007;Lauterwein et al, 1995;Lawrey, 1989;Manojlovic et al, 2011). More specifically, studies have shown that lichen compounds either in crude extract or as purified compounds are not active against Gram-negative bacteria such as E. coli and P. aeruginosa (Francolini et al, 2004;Ingólfsdóttir, 2002;Lauterwein et al, 1995;Melgarejo et al, 2008;Paudel et al, 2012;Yilmaz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usnic acid has antibiotic properties, both the natural enantiomers being active against Gram positive bacteria on susceptible and resistant strains . A more intense bacteriostatic rather than bactericidal action was reported on some metal complexes of usnic acid hydrazones …”
Section: Introductionmentioning
confidence: 99%